2013
DOI: 10.1016/j.radonc.2013.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy for localized prostate cancer: Pooled analysis from a multi-institutional consortium of prospective phase II trials

Abstract: PSA relapse-free survival rates after SBRT compare favorably with other definitive treatments for low and intermediate risk patients. The current evidence supports consideration of SBRT among the therapeutic options for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
302
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 422 publications
(321 citation statements)
references
References 21 publications
11
302
2
6
Order By: Relevance
“…All of the treatment plans developed using each collimator type met the critical organ dose constraint requirements set forth in a previous report 5. In the MLC plans, V50% for the bladder is about 30% lower than it is in the circular collimator plans, and this difference is statistically significant.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…All of the treatment plans developed using each collimator type met the critical organ dose constraint requirements set forth in a previous report 5. In the MLC plans, V50% for the bladder is about 30% lower than it is in the circular collimator plans, and this difference is statistically significant.…”
Section: Resultsmentioning
confidence: 87%
“…The prescription dose was 36.25 Gy in 95% of the PTV and was delivered in five fractions, as in extreme hypofractionated radiation therapy. The parameters, such as the PTV margin, prescription dose, and treatment fraction number, were identical to those used in the prospective phase II trials conducted by King et al5 Moreover, the dose – volume histogram (DVH) goals used for the critical tissues, which are described hereinafter, were set in accordance with those reported by King et al5 The rectum DVH goals were V50% < 50% (i.e., the volume receiving 50% of the prescribed dose was <50%), V80% < 20%, V90% < 10%, and V100% < 5%. The bladder DVH goals were V50% < 40% and V100% < 10%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we looked specifically at the consequences of limiting the upper dose to the PTV for low‐ and intermediate‐risk prostate cancer VMAT treatment plans. We investigated this site because (a) ablative doses are generally acceptable for prostate radiation therapy,8, 9, 10, 11, 12 which suggests minimal risk of toxicity from overdosing the PTV exclusively (within reason), (b) it is a site suggested by Craft et al.,5 and (c) prostate treatments are extremely common and make up a major fraction of the clinical workload for many clinics. We conducted a treatment planning study with a cohort of 17 anonymized VMAT patients using our clinical protocol for prostate cancer patients and compared optimization with and without an upper dose constraint on the PTV, which would be thought to be the best case scenario in terms of OAR sparing.…”
Section: Introductionmentioning
confidence: 99%
“…These have shown that 20–28 days fractionation schedules result in approximately equivalent biochemical control and rectal toxicities compared with 37–39 days conventional fractionation regimens. Stereotactic body radiation therapy (SBRT) has been increasingly explored for prostate treatment, often on a platform including some degree of real‐time imaging to reduce the impact of intrafraction motion 6. The need for such specialised equipment may impede the wider application of prostate SBRT in the community setting.…”
Section: Introductionmentioning
confidence: 99%